Integrated Analysis of Key Genes and Pathways Involved in Nonalcoholic Steatohepatitis Improvement After Roux-en-Y Gastric Bypass Surgery - Chen, Fu; Zhou, Yong; Wu, Zhiyuan; Li, Yunze; Zhou, Wenlong; Wang, Yong (Frontiers in Endocrinology, 2021)
Background: As the incidence of nonalcoholic fatty liver disease (NAFLD) increases globally, nonalcoholic steatohepatitis (NASH) has become the second common cause of liver transplantation for liver diseases. Recent evidence shows that Roux-en-Y gastric bypass (RYGB) surgery obviously alleviates NASH. However, the mechanism underlying RYGB induced NASH improvement is still elusive. Methods: We obtained datasets, including hepatic gene expression data and histologic NASH status, at baseline and one year after RYGB surgery. Differentially expressed genes (DEGs) were identified comparing gene expression before and after RYGB surgery in each dataset. Common DEGs were obtained between both datasets and further subjected to functional and pathway enrichment analysis. Protein-protein interaction (PPI) network was constructed, and key modules and hub genes were also identified. Results: In the present study, GSE106737, and GSE83452 datasets were included. One hundred thirty common DEGs (29 up-regulated and 101 down-regulated) were identified between GSE106737 and GSE83452 datasets. KEGG analysis showed that mineral absorption, IL-7 signaling pathway, osteoclast differentiation, and TNF signaling pathway were significantly enriched. Based on the PPI network, IGF1, JUN, FOS, LDLR, TYROBP, DUSP1, CXCR4, ATF3, CXCL2, EGR1, SAA1, CTSS, and PPARA were identified as hub genes, and three functional modules were also extracted. Conclusion: This study identifies the global gene expression change in the liver of NASH patients before and after RYGB surgery in a bioinformatic method. Our findings will contribute to the understanding of molecular biological changes underlying NASH improvement after RYGB surgery.